Morituri: Three One-Act Plays : Teja$1 (BFritzchen$1 (BThe Eternal Masculines - Sudermann, Hermann, 1857-1928; Alexander, Archibald, 1855-1917 (Salt Lake City, UT : Project Gutenberg, 2010)
"Morituri: Three One-Act Plays" by Hermann Sudermann is a collection of dramatic works likely written in the early 20th century. The plays delve into themes of conflict, existentialism, and human relationships, portraying the struggles and emotions of their characters against the backdrop of society's pressures. The first play, "Teja," introduces a somber king who grapples with his sense of duty and the tragic fate of his people, setting a serious tone for the collection. The opening of "Teja" depicts a tense scene in the king's tent, where King Teja, surrounded by his advisors and his new bride, Balthilda, reflects on the dire circumstances facing his kingdom. As they await the arrival of ships laden with supplies, the hunger and weariness of the warriors are palpable. Teja struggles with his identity as a ruler amidst despair, contemplating the weight of his responsibilities and the choices he must make leading to a battle. The atmosphere is filled with a sense of impending doom, as Teja faces the reality that he may no longer be able to fulfill his kingly duties, establishing a powerful narrative steeped in emotional conflict and societal collapse. (This is an automatically generated summary.)
Release date is 2010-11-18
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: German drama -- Translations into English